Τhe rational decision-making and the social responsibility in the optimal functioning of the school - Christos Kanavas; Sotiria Triantari (Cogent Social Sciences)
This article discusses the concept of school leadership under the prism of decision-making by school principals. Effective and modern school leadership requires integrating all aspects of management so as to benefit students and teachers providing a safe, respectful, and supportive environment. Meeting the requirements that influence the decision-making process and incorporating a suitable management model enables the principal to allow not only the school and staff but also students to reach their full potential. The overall success of a school depends on its management and informed decisions regarding interventions that promote social responsibility. Findings of this study revealed that headmasters are considered rational decision makers with ethical parameters and emotional intelligence and that optimal decision-making is affected by the interpersonal relationships between the principal and teachers.